2007
DOI: 10.1016/j.scriptamat.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of applied stresses on the equilibrium moisture content in polymers

Abstract: To cite this version:Katell Derrien, Pierre Gilormini. The effect of applied stresses on the equilibrium moisture content in polymers. Scripta Materialia, Elsevier, 2007, 56 (4) Abstract -The relation between saturation moisture content in a polymer and applied stresses is derived as a function of the coefficient of moisture expansion. The model predictions are compared favourably with experimental data taken from the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Later, in Section 3.2, we consider 3 Alternatively, one may adopt a normalized analogy [36], which can be used under a generalized case of a bi-material system where both the phases are pervious. 4 The operation A:B denotes a contracted product between two tensors or between a tensor and a vector. the cases where the moisture and mechanical bc's are applied sequentially.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, in Section 3.2, we consider 3 Alternatively, one may adopt a normalized analogy [36], which can be used under a generalized case of a bi-material system where both the phases are pervious. 4 The operation A:B denotes a contracted product between two tensors or between a tensor and a vector. the cases where the moisture and mechanical bc's are applied sequentially.…”
Section: Resultsmentioning
confidence: 99%
“…Composites used for dental restoration purposes may experience aqueous service environments that range between strongly acidic to strongly alkaline [3]. Further, the moisture diffusivity itself may be a function of the applied stress, which in turn may affect the stress distribution in the composite [4][5][6]. The absorbed moisture may lead to matrix cracking [7][8][9][10][11] or plasticize the matrix thereby reducing effective stiffness and strength of polymers [7] and their composites [1,2,12].…”
Section: Introductionmentioning
confidence: 99%
“…The opposite was found in experiments with clay-bearing stone conducted by Scherer and Jimenez Gonzalez [27]; a delay in the post-peak flattening resulted from the dry side being compressed by bending stresses, making it more difficult for water to cause swelling. The stresses which develop due to the bending can have an influence on the moisture transport due to their impact on the chemical potential of water and thus the moisture absorption capacity of the matrix [38]. Since a gradient in chemical potential is the driving force for moisture transport, stresses arising from swelling and shrinkage can have an influence on the moisture distribution over time [39], which again influence the bending.…”
Section: Step Responsementioning
confidence: 99%
“…Therefore, models have been developed to predict the multi-scale mechanical states occurring during both the transient stage and the permanent regime of the moisture diffusion process of organic matrix composites submitted to hygro-mechanical loads [10][11][12][13][14]. In this field of research, the most recent investigations [15][16][17][18][19] focus upon taking into account, in the theoretical approaches, various features of hygro-mechanical coupling, especially the dependence of both the moisture diffusion coefficient and the maximum moisture absorption capacity on the mechanical states (strains and stresses), as shown, for instance, in [20][21][22][23][24]. More recent works, made by Autran et al [25] and Wan et al [26], have experimentally demonstrated the influence of mechanical loading on the moisture diffusion behavior.…”
Section: Introductionmentioning
confidence: 99%